Generasi Millenial dan Resep Kuliner Tradisional sebagai Budaya Bangsa Indonesia - Setya Putri Erdiana (DeKaVe, 2018)
Abstract.Indonesia is one of the most cultured countries in the world and one of them is traditional culinary. On the other hand, Indonesian traditional culinary is now being displaced and replaced by fast food or culinary from other countries. And lately, traditional culinary is hard to find especially in big cities, it shows that interest of it decreases and only few who can cook the traditional culinary. This is the effect of the generation itself because each generation influences society. Now, millennial generation is the most influential generation, because most of them are in the productive age of 19-35 years old. Aside from being the next generation, millennial generation is also considered to be the generation that has the most influence on the emerging trends in society. Especially the use of gadgets and technology nowadays, causing them to be called instant generation, which is the opposite to people's perceptions of traditional culinary that is complicated to make and requires a long cooking time. By using qualitative research methods, it is expected to obtain data as accurately as possible with the facts and conditions. By observing and interviewing the target audience to gather information about the community's perspective on Indonesian culinary and the cooking process, also gathering theories to support the research process. Thus, the results of this study are expected to provide concept of culinary recipes traditional form of design that can be used in designing traditional recipe application that attracts millennials to cook traditional Indonesian culinary.Key words:millenial generation, recipe, traditional Indonesian culinary